Fasting in Islam: A Combination of Spiritual Elevation and Prevention of Diseases - Ali Khan, Muhammad Muzaffar; M.Nor, Noraisha; Mamat, Nik Mazlan; Mohd-Shukri, Nor Azwani; Abu Bakar, Wan Azdie Mohd (IIUM Medical Journal Malaysia, 2018)
The obligatory fasting of Ramadan is not only an Islamic ritual to enhance the God-consciousness (called Taqwa), it may also lead to improvement of health status of fasting person(s). In other words, it is a complete overhauling instrument of Muslims soul/body in terms of faith and health. This can be termed as “Islamic fasting: a combination of spiritual elevation and prevention of diseases”. During fasting Muslims try to maintain integrity of the human body both physically and spiritually. It not only keeps us healthy physically/spiritually but also makes us healthy in social obligations. Furthermore, with full devotion it brings long-lasting changes in the individual’s life and relate to the level of righteousness and strength of character to resist desires. In health fasting plays an important role, for example the improvement of hyperlipidemia, obesity (fat loss), diabetes, cognition, cell functions, immunological factors, inflammation, stress and lifespan etc. This article is an effort to review and discuss research carried out on the listed conditions during the holy month of Ramadan on various aspects of human health.